Eliciting participant perspectives about a mailed brochure on sleeping pills and cognitive behavioural therapy for insomnia to inform future implementation of deprescribing interventions - Selene S Mak; Aaron P Thomas; Cathy A Alessi; Jennifer L Martin; Christi Ulmer; Christopher N Kaufmann; Jason P Smith; Constance H Fung (International Journal of Pharmacy Practice, 2026)
Abstract Objectives To explore how older adults engaged with a direct-to-patient brochure and telephone reinforcement call about benzodiazepine receptor agonist (BZRA) risks and discontinuation, including barriers and facilitators to acting on brochure content. Methods This qualitative analysis was conducted within a 3-arm pilot randomized trial at 2 Veterans Health Administration facilities. Participants randomized to the active brochure plus telephone reinforcement call arm (n = 120) were contacted up to two times. Field notes from completed calls were analysed using qualitative content analysis. Key findings Seventy-two participants completed a call. Three themes emerged: brochure awareness and interest, intention to act on brochure content, and perceptions of insomnia and BZRAs. Participants varied in whether they recalled or reviewed the brochure, whether they planned to discuss BZRA use with a clinician or use digital cognitive behavioural therapy for insomnia, and how they understood long-term BZRA use. Conclusions Limited recall of mailed materials, digital access barriers, and beliefs about BZRA use may shape engagement with low-touch deprescribing interventions.